PENGARUH PERSON ORGANIZATION FIT DAN LOCUS OF CONTROL DENGAN MEDIASI KOMITMEN ORGANISASIONAL TERHADAP KINERJA PADA PEGAWAI DINAS PENDIDIKAN KABUPATEN REMBANG (Jurnal Mahasiswa Pasca Sarjana, 2014)
Performanceis basically anoutcomeachievedbyworkingaccording tostandardsorcriteriaestablished in accordancewith thespecific job. In the implementation, the performanceis affectedbyseveralfactors, such asPersonOrganizationFit, Locus ofControlandOrganizationalCommitment. This study aimstoanalyzethe directeffect ofPersonOrganizationFit, Locus ofControlandOrganizationalCommitmentto employee performanceandinfluence ofPersonOrganizationFitandLocus ofControlon employee performanceindirectly, through mediating variablesof OrganizationalCommitmenton Dinas Pendidikan Kabupaten Rembang. The populationin this study wereall employees Dinas Pendidikan Kabupaten Rembang whichhas statusof Civil Servants(PNS) as many as128employees. Researchtechniqueused isthepurposive samplingmethodandnumberof samples taken105respondents. Mechanicaltestingdata usedin this study includethe validity ofthefactor analysis, Cronbach alphareliability test, ModelTest, RegressionAnalysis, HypothesisTestingandTestMediation. The results showedthat thevariablePersonOrganizationFit, Locus ofControlandOrganizationalCommitmenthas apositive impacton performance. OrganizationalCommitmentdoes notmediatePersonOrganizationFit on performance and OrganizationalCommitmentdoes notmediateLocus ofControlon performance. Keywords:PersonOrganizationFit, Locus ofControlandOrganizationalCommitmentand Employee Performance